Ego- and allo-network disconnection underlying spatial disorientation in subjective cognitive decline. (April 2021) - Chen, Qian; Qing, Zhao; Jin, Jiaxuan; Sun, Yi; Chen, Wenqian; Lu, Jiaming; Lv, Pin; Liu, Jiani; Li, Xin; Wang, Junxia; Zhang, Wen; Wu, Sichu; et al.
Abstract: Patients with Alzheimer's disease (AD) related dementia and mild cognitive impairment experience difficulties with spatial navigation (SN). However, SN has rarely been investigated in individuals with subjective cognitive decline (SCD), a preclinical stage with elevated progression rate to symptomatic AD. In this study, 30 SCD subjects and 30 controls underwent cognitive scale (CS) evaluation, a 2D computerized SN test, and resting-state functional magnetic resonance imaging scanning. Two SN brain networks (ego-network and allo-network), each with 10 selected spherical regions, were defined. We calculated the average network functional connectivity (FC) and region-to-region FC within the two networks and evaluated correlations with SN performance. Compared with the controls, the SCD group performed worse in the SN test and showed decreased FC between the right retrosplenial and right prefrontal cortices in the ego-network, and between the right retrosplenial cortex and right hippocampus in the allo-network. The logistic regression model based on SN and FC measures revealed a high area under the curve of .880 in differentiating SCD individuals from controls. These results suggest that SN network disconnection contributes to spatial deficits in SCD, and SN and FC measures could benefit the preclinical detection of subjects with incipient AD dementia.